Enhanced upconversion emission in ZrO2–Al2O3 composite oxide. Issue 15 (14th March 2016) - Cong, Yan; Dong, Bin; Yu, Naisen; He, Yangyang; Zhao, Ying; Yang, Yang
Abstract : Significant enhancement of the UC emission in ZrO2 –Al2 O3 solid solutions samples was obtained compared to the pristine oxide samples—ZrO2 and Al2 O3 . Abstract : Aqueous solutions of zirconium oxychloride and aluminum nitrate were coprecipitated and crystallized to form a ZrO2 –Al2 O3 solid solution. The upconversion (UC) emission from different Er 3+ -doped samples was studied. An enhancement of the green UC emission by as much as 22 times was achieved by co-doping with Yb 3+ and Mo 6+ ions due to an energy transfer at a higher excited-state energy, which partly avoided the non-radiative decay processes at the lower energy levels of Er 3+ . The UC emission of the ZrO2 –Al2 O3 composite system series doped with different agents was enhanced. Excess oxygen vacancies are generated by forming ZrO2 –Al2 O3 solid solutions, which have an energy level close to the 4 F7/2 level of the Er 3+ ions. The defect state promoted the energy transfer process resulting in an eight-fold increased green UC emission in ZrO2 –Al2 O3 solid solutions. The solid solutions have a superior color chromaticity of x = 0.25 and y = 0.71 due to the evident enhancement in the green to red emission ratio in the 8ZrO2 –2Al2 O3 sample.